2002
DOI: 10.1002/jmri.10047
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation with gray‐scale connectedness can separate arteries and veins in MRA

Abstract: Purpose:To describe and present some preliminary results for a novel algorithm for segmentation with gray-scale connectedness as a means to separate arteries and veins in magnetic resonance angiography (MRA). Materials and Methods:The proposed algorithm, SeparaSeed, uses the gray-scale degree of connectedness as a tool to find the zone surrounding each vessel, in order to split the original volume into its different vessel components. In contrast to traditional segmentation methods, no gray-scale information i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…Another approach for artery/vein segmentation is based on different types of connectivity algorithms (13)(14)(15)(17)(18)(19)22), which utilizes a high-resolution dataset to segment out the arteries and veins. It exploits the geometrical characteristics of the arterial and venous vessel trees, comparing the brightness of every voxel with its neighbors and thus deciding whether they belong to the same structure or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach for artery/vein segmentation is based on different types of connectivity algorithms (13)(14)(15)(17)(18)(19)22), which utilizes a high-resolution dataset to segment out the arteries and veins. It exploits the geometrical characteristics of the arterial and venous vessel trees, comparing the brightness of every voxel with its neighbors and thus deciding whether they belong to the same structure or not.…”
Section: Discussionmentioning
confidence: 99%
“…Different postprocessing strategies have been proposed to deal with this task (12)(13)(14)(15)(16)(17)(18)(19). The most commonly applied is the simple subtraction of the arterial datasets from venous datasets.…”
mentioning
confidence: 99%
“…Building on our earlier work on "virtual contrast injection" visualization [5][6][7], this paper presents a quantitative coronary CTA analysis tool, built on the open-source PACS workstation software OsiriX [8], which integrates both fully automatic and interactive methods for coronary artery extraction. The computational power of an ordinary PC is exploited by running the non-supervised coronary artery segmentation and centerline tracking in the background as soon as the images are received.…”
mentioning
confidence: 99%
“…Interactive approaches may solve part of this problem but can be very time-consuming. The concept of fuzzy connectedness (greyscale connectedness), which has been proposed to separate arteries and veins in Magnetic resonance angiography (MRA) [5][6][7], shows great ability to separate two contrastfilled structures from each other. A previous feasibility study showed that this approach can be applied to 3D CTA data to separate the coronary arteries from other contrast-filled structures and thus permit coronary artery visualization in an angiographic mode similar to invasive X-ray angiography [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to overcoming several problems of former algorithms [5][6][7], the new algorithm includes automated extraction of the vessel centerline, which is useful, e.g., for creating CPR images.…”
Section: Introductionmentioning
confidence: 99%